Myopia. Part I – pathogenesis of current state of knowledge - Oleszczyńska-Prost, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
It is now clear that the genetics and environment both play a role in the development of myopia. Along with genotype, daylight is another key factor to affect the development of the eye as an optical system. Other environmental factors, such as miscorrected refractive error, excessive near work, insufficient physical activity, sleep or rest, as well as poorly balanced diet and lifestyle (stress) have also been implicated in worsening of myopia.